LEGAL ASPECTS OF FIGHTING COVID-19 ON THE AFRICAN CONTINENT - Макарчук, Ксенія (SWorldJournal, 2025)
The article examines the set of legal measures taken by African governments to counter the COVID-19 pandemic. The author analyses the administrative and legal means of combating the pandemic and the effectiveness of these steps to slow down the spread of